2020
DOI: 10.1007/s10654-020-00611-w
|View full text |Cite
|
Sign up to set email alerts
|

Are infectious diseases risk factors for sarcoidosis or a result of reverse causation? Findings from a population-based nested case–control study

Abstract: Findings from molecular studies suggesting that several infectious agents cause sarcoidosis are intriguing yet conflicting and likely biased due to their cross-sectional design. As done in other inflammatory diseases to overcome this issue, prospectivelycollected register data could be used, but reverse causation is a threat when the onset of disease is difficult to establish. We investigated the association between infectious diseases and sarcoidosis to understand if they are etiologically related. We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…During this time, patients are under frequent follow-up and ∼40% receive immunosuppressants [ 10 ]. As indicated in sensitivity analyses and previous research [ 12 ], the peak in serious infection risk could be partly explained by the increased healthcare interaction, or possibly a lower threshold of hospitalisation for infection. However, our analyses suggested that initiation of immunosuppressants, particularly that of systemic corticosteroids, remains a major risk factor for serious infection in sarcoidosis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…During this time, patients are under frequent follow-up and ∼40% receive immunosuppressants [ 10 ]. As indicated in sensitivity analyses and previous research [ 12 ], the peak in serious infection risk could be partly explained by the increased healthcare interaction, or possibly a lower threshold of hospitalisation for infection. However, our analyses suggested that initiation of immunosuppressants, particularly that of systemic corticosteroids, remains a major risk factor for serious infection in sarcoidosis.…”
Section: Discussionmentioning
confidence: 77%
“…During this time, patients are under frequent follow-up and ∼40% receive immunosuppressants [10]. As indicated in sensitivity analyses and previous research [12], the peak in serious infection risk could be partly explained FIGURE 1 Risk of first serious infection in individuals with sarcoidosis (overall and stratified by treatment status around diagnosis) and their general population comparators. Treatment data were available for individuals with sarcoidosis entering the cohort starting 2006, hence follow-up for those was shorter than overall sarcoidosis and the general population comparators.…”
Section: Discussionmentioning
confidence: 85%
“…Among bacterial antigens, Cutibacterium acnes was identified in cultures of sarcoid lesions, and remnants of Mycobacterium tuberculosis were found in granulomas [23,24]. Epidemiological studies on the role of these and other infections show conflicting results [25,26]. It is important to acknowledge that bias due to reverse causation is likely because latent sarcoid inflammation increases the risk of infections before diagnosis [26].…”
Section: Antigensmentioning
confidence: 99%
“…[22][23][24] However, whether infection contributes to the development of sarcoidosis is unknown. [22][23][24][25] Autoimmunity may contribute to the development of sarcoidosis. Vimentin, a structural protein coded by the VIM gene may be implicated in the development of sarcoidosis.…”
Section: Pathogenesis Of Sarcoidosismentioning
confidence: 99%
“…Microbes, such as Propionibacterium species and Mycobacterium , have been associated with the presence of sarcoidosis . However, whether infection contributes to the development of sarcoidosis is unknown . Autoimmunity may contribute to the development of sarcoidosis.…”
Section: Pathogenesis Of Sarcoidosismentioning
confidence: 99%